Ethnic Diversity and Preferences for Redistribution: Reply - Matz Dahlberg; Karin Edmark; Helene Lundqvist (Research Institute of Industrial Economics (IFN), 2013)
In a comment to Dahlberg, Edmark and Lundqvist (2012), Nekby and Pettersson-Lidbom (2012) argue (i) that the refugee placement program should be measured with contracted rather than actually placed refugees, and claim that the correlation between the two measures is insignificant and close to zero; (ii) that instead of using the rotating individual panel, we should have used the full cross-sections in combination with municipality fixed effects; and (iii) that immigrants should be defined based on country of birth rather than citizenship. In this response, we discuss why we (i) do not agree that contracted refugees is the preferred measure, and we show that the correlation between the two measures is highly significant and large; (ii) do not agree that the full cross-sections can be used; and (iii) do agree that defining immigrants according to country of birth is preferred. In a re-analysis, the conclusion from Dahlberg, Edmark and Lundqvist (2012) that ethnic diversity has a statistically and economically significant negative effect on preferences for redistribution is only marginally affected.
Keywords: D31; D64; I30; Z13; 330; Income redistribution; Ethnic heterogeneity; Immigration